Deepening Our Knowledge about Sustainability Education in the Early Years: Lessons from a Water Project - Maria Ampartzaki; Michail Kalogiannakis; Stamatios Papadakis (MDPI AG, 2021)
The transformative agenda of sustainability education constitutes the focus of early-years education. In quality sustainability educational projects, children are supported to draw links between nature and society and relate to the studied phenomena. Is this methodological approach realized in educational programs for the early years? The present work presents some of the significant findings of a case study on implementing a water project in early-year settings around Europe. It explores the characteristics and the methodological approaches the project implementation developed. Three types of implementation are derived from the qualitative analysis of data and reveal that there are still cases in which sustainability projects are focused on a descriptive approach rather than critical inquiry and analysis. In this sense, the need for educational designs that help children deepen their understanding of sustainability issues and become empowered citizens who will work for a sustainable future is highlighted.